Improved properties and salt rejection of polysulfone membrane by incorporation of hydrophilic cobalt-doped ZnO nanoparticles - Muneer M. Ba-Abbad (14151660) (2024)
In this study, the nanoparticles (NPs) of ZnO and Co2+ ions doped ZnO (doped ZnO) were incorporated into a matrix of polysulfone (PSf) membranes to enhance their surface properties prepared using a simple wet phase inversion technique. The hybrid PSf membranes were fabricated with 0.5 wt. % of ZnO and doped ZnO NPs. These membranes were characterized using XRD, TGA, FESEM-EDX, and salt rejection performance. The hydrophilicity of PSf membranes was improved by adding of ZnO and doped ZnO NPs which showed a decrease in contact angle values from 82° to 62° with an increased flux with water. Among the prepared membranes, doped ZnO NPs showed the highest salt rejection for both sodium chloride (NaCl) and sodium sulfate (Na2SO4) compared to pure PSf and PSf with ZnO NPs which confirm the improvement contact angle and water permeability. Overall, the results of this study showed that embedding a small amount of Co2+ ions doped ZnO NPs with PSf has significant potential to be applied in industrial-scale membrane applications. Other Information Published in: Emergent Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s42247-023-00613-w